Antiretroviral therapy and vaginally administered contraceptive hormones: a three-arm, pharmacokinetic study. Issue 9 (September 2019) - Scarsi, Kimberly K; Cramer, Yoninah S; Rosenkranz, Susan L; Aweeka, Francesca; Berzins, Baiba; Coombs, Robert W; Coughlin, Kristine; Moran, Laura E; Zorrilla, Carmen D; Akelo, Victor; Aziz, Mariam; Friedman, Ruth K; et al.
Summary: Background: Drug-drug interactions between orally administered antiretroviral therapy (ART) and hormones released from an intravaginal ring are not known. We hypothesised that ART containing either efavirenz or ritonavir-boosted atazanavir would alter plasma concentrations of vaginally administered etonogestrel and ethinylestradiol but that ART concentrations would be unchanged during use of an intravaginal ring. Methods: We did a parallel, three-group, pharmacokinetic evaluation at HIV clinics in Asia (two sites), South America (five), sub-Saharan Africa (three), and the USA (11) between Dec 30, 2014, and Sept 12, 2016. We enrolled women with HIV who were either ART-naive (control group; n=25), receiving efavirenz-based ART (n=25), or receiving atazanavir–ritonavir-based ART (n=24). Women receiving ART were required to be on the same regimen for at least 30 days, with 400 copies or less per mL of plasma HIV-1 RNA; women not receiving ART had CD4 counts of 350 cells per μL or less. We excluded participants who had a bilateral oophorectomy or conditions that were contraindicated in the intravaginal ring product labelling. An intravaginal ring releasing etonogestrel and ethinylestradiol was inserted at entry (day 0). Single plasma samples for hormone concentrations were collected on days 7, 14, and 21 after intravaginal ring insertion. The primary outcome was the plasma concentration of etonogestrel and ethinylestradiol on day 21. Etonogestrel and ethinylestradiol concentrations were compared between each ART group and the control group by geometric mean ratio (GMR) with 90% CIs and Wilcoxon rank-sum test. As secondary outcomes, efavirenz or ritonavir-boosted atazanavir concentrations were assessed by 8-h intensive pharmacokinetic sampling at entry before intravaginal ring insertion and before intravaginal ring removal on day 21. Antiretroviral areas under the concentration-time curve (AUC0–8 h ) were compared before and after intravaginal ring insertion by GMR (90% CI) and Wilcoxon signed-rank test. This study is registered withClinicalTrials.gov, numberNCT01903031 . Findings: Between Dec 30, 2014, and Sept 12, 2016, we enrolled 84 participants in the study; ten participants were excluded from the primary hormone analysis. 74 participants met the primary endpoint: 25 in the control group, 25 in the efavirenz group, and 24 in the atazanavir group. On day 21 of intravaginal ring use, participants receiving efavirenz had 79% lower etonogestrel (GMR 0·21, 90% CI 0·16–0·28; p<0·0001) and 59% lower ethinylestradiol (0·41, 0·32–0·52; p<0·0001) concentrations compared with the control group. By contrast, participants receiving ritonavir-boosted atazanavir had 71% higher etonogestrel (1·71, 1·37–2·14; p<0·0001), yet 38% lower ethinylestradiol (0·62, 0·49–0·79; p=0·0037) compared with the control group. The AUC0–8 h of efavirenz or atazanavir did not differ between the groups. Interpretation: Hormone exposure was significantly lower when an intravaginal ring contraceptive was combined with efavirenz-based ART. Further studies designed to examine pharmacodynamic endpoints, such as ovulation, when intravaginal ring hormones are combined with efavirenz are warranted. Funding: National Institutes of Health, through the AIDS Clinical Trials Group and the International Maternal Pediatric Adolescent AIDS Clinical Trials Network, National Institute of Allergy and Infectious Diseases, Eunice Kennedy Shriver National Institute of Child Health and Human Development, and the National Institute of Mental Health.